Rigorous DAP in the early years from theory to practice - Brown, Christopher Pierce; Feger, Beth Smith; Mowry, Brian Nelson (St. Paul, MN Redleaf Press, 2019)
RIGOROUS DAP in the Early Years: From Theory to Practice provides teachers with a roadmap for teaching that helps children meet academic expectations and maintains focus on the appropriate development of the whole child. A construct of eleven practices, RIGOROUS DAP supplies teachers with strategies for 1) making instructional decisions that meet the needs of the individual child; 2) sustaining culturally relevant practices; 3) engaging stakeholders in conversations about educating young children for school success through practices that attend to their individual, sociocultural, and developmental needs; and 4) ensuring all children experience high-level learning and succeed in school. An academically rigorous learning environment allows all children to learn at high levels through hands-on learning experiences that address the whole child and connect to the child's world in and out of school. A developmentally appropriate learning environment considers the children's developmental, cognitive, social, emotional, linguistic, and physical development, as well as the sociocultural worlds in which they live.--Adapted from Amazon.
Why rigorous dap is needed -- Examining how children develop and learn across all developmental domains -- Knowing your students' worlds -- Teaching to all developmental domains -- Knowing your teaching context -- Monitoring students' achievement -- Integrating content areas through quality educational experiences -- Moving forward to ensure all children engage in rigorous dap.
"Ages 3 to 8"--Cover.
Includes bibliographical references and index.
Keywords: Early childhood education